Alcohol retail privatisation in Canadian provinces between 2012 and 2017. Is decision making oriented to harm reduction?. (14th December 2020) - Giesbrecht, Norman; Wettlaufer, Ashley; Stockwell, Tim; Vallance, Kate; Chow, Clifton; April, Nicole; Asbridge, Mark; Callaghan, Russell; Cukier, Samantha; Hynes, Geoff; Mann, Robert E.; Solomon, Robert; et al.
Abstract: Introduction: Policy changes may contribute to increased alcohol‐related risks to populations. These include privatisation of alcohol retailing, which influences density of alcohol outlets, location of outlets, hours of sale and prevention of alcohol sales to minors or intoxicated customers. Meta‐analyses, reviews and original research indicate enhanced access to alcohol is associated with elevated risk of and actual harm. We assess the 10 Canadian provinces on two alcohol policy domains—type of alcohol control system and physical availability of alcohol—in order to track changes over time, and document shifting changes in alcohol policy. Methods: Our information was based on government documents and websites, archival statistics and key informant interviews. Policy domains were selected and weighted for their degree of effectiveness and population reach based on systematic reviews and epidemiological evidence. Government representatives were asked to validate all the information for their jurisdiction. Results: The province‐specific reports based on the 2012 results showed that 9 of 10 provinces had mixed retail systems—a combination of government‐run and privately owned alcohol outlets. Recommendations in each provincial report were to not increase privatisation. However, by 2017 the percentage of off‐premise private outlets had increased in four of these nine provinces, with new private outlet systems introduced in several. Discussion and Conclusions: Decision‐making protocols are oriented to commercial interests and perceived consumer convenience. If public health and safety considerations are not meaningfully included in decision‐making protocols on alcohol policy, then it will be challenging to curtail or reduce harms.